A Clinical Study on Congenital Diaphragmatic Hernia In Neonates - Siraj Nabi, Muhammad Daraz Khan, Sadaf Saeed Shami, Nasrul Huda, Ashok Kumar, Muhammad Ibrahim, Zeeshan Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Congenital diaphragmatic hernia (CDH) is a severe and life-threatening condition in neonates, characterized by the abnormal development of the diaphragm, allowing abdominal organs to herniate into the chest cavity. This leads to lung hypoplasia, pulmonary hypertension, and respiratory distress. CDH has an incidence rate of approximately 1 in 2,500 live births, with left-sided hernias being more common. The aim of this study was to evaluate the clinical outcomes, risk factors, and long-term prognosis of neonates diagnosed with congenital diaphragmatic hernia. Objective: To analyze the clinical presentation, surgical interventions, and post-operative outcomes of neonates with congenital diaphragmatic hernia (CDH), focusing on survival rates, complications, and long-term developmental progress. Methodology: A total of 105 neonates diagnosed with congenital diaphragmatic hernia were enrolled. The study included data on prenatal diagnosis, post-natal interventions, surgical outcomes, and the incidence of complications. Data were collected retrospectively from medical records. Statistical analysis included descriptive statistics, chi-square tests, and survival analysis. Results: Of the 105 neonates, 78% underwent successful surgical repair of the diaphragm, with a survival rate of 85% at discharge. The most common complication was pulmonary hypertension (35%), followed by gastroesophageal reflux (20%). Prenatal diagnosis improved survival rates, with neonates diagnosed prenatally having an 88% survival rate, compared to 81% in those diagnosed postnatally. Left-sided CDH was more common (65%) and had a better prognosis than right-sided CDH (35%). Conclusion: Congenital diaphragmatic hernia remains a challenging condition, but early diagnosis, surgical intervention, and management of complications significantly improve survival and long-term outcomes. The study highlights the importance of prenatal screening, and pulmonary management, which may reduce complications and improve the prognosis for affected neonates. Keywords: Congenital diaphragmatic hernia, neonates, surgery, pulmonary hypertension, prenatal diagnosis, survival rate, complications.